The effect of Allium sativum in experimental peritoneal adhesion model in rats - Topal,Uğur (2019)
Abstract Purpose: To evaluate the effect of garlic on formation of postoperative adhesions in rats. Methods: Twenty-four Sprague dawley rats were divided into three groups. In Group 1 (sham), laparotomy was performed and stitched up. In Group 2 (control), after laparotomy was performed, punctate hemorrhage was induced by cecal abrasion in the cecum and 2 cc of saline was intraperitoneally administered to each rat. In Group 3 (experimental), after laparotomy was performed, punctate hemorrhage was induced by cecal abrasion in the cecum and each rat was intraperitoneally administered a sterile Allium sativum derivative. The rats in all groups were re-laparotomized on postoperative day 7; samples were obtained from the peritoneal tissue surrounding the cecum Results: In Group 3, there was a statistically significant difference in terms of inflammation, lymph node size, and free oxygen radicals; these parameters tended to increase. In terms of fibrosis evaluated using H&E and MT, there was no significant difference between groups 2 and 3. Conclusions: No positive outcomes indicating that Allium sativum reduces intra-abdominal adhesions were obtained. However, it caused severe inflammation in the tissue. Additionally, in immunohistochemical analyses conducted to detect oxidative stress, allium sativum increased the production of free oxygen radicals in the tissue.